Thermodynamics of the d = 3 + 1 quantum XY model. (14th September 2016) - Hofmann, Christoph P
Abstract: Within effective field theory we explore the properties of the d = 3 + 1 quantum XY model at low temperatures and in weak magnetic or staggered fields. For this parameter regime only few results appear to be known, and furthermore are restricted to one-loop order. In the present study we systematically analyze the thermodynamics of the d = 3 + 1 quantum XY model up to three-loop order. In the low-temperature expansion of the free energy density, the free Bose gas term of order T 4 receives corrections of order T 6 and T 8 . The discussion also includes the pressure, (staggered) magnetization and susceptibility. In particular, we show how these quantities are influenced by the spin-wave interaction.